THE EFFECT OF CLIMATE CHANGE ON STOCK MARKET INDICES IN IRAQ - Hussein Hadi Abdulameer (Scholars Digest Publishing, 2023)
Climate change can have a significant impact on stock market indices, with both direct and indirect effects. Direct effects include physical damage to infrastructure and property caused by extreme weather events such as hurricanes, floods, and wildfires. Such events can disrupt supply chains, reduce productivity, and increase costs, leading to lower profits for companies and, in turn, lower stock prices. Indirect effects of climate change can be seen through changes in regulations and consumer behavior. For example, as governments and consumers become increasingly concerned about the environment, they may demand stricter regulations on carbon emissions and other environmental practices. This can lead to increased costs for companies that do not comply, and a shift in consumer behavior towards more sustainable products and services. Companies that are slow to adapt may see a decline in their stock prices. Temperature and precipitation were taken as independent variables for the research, against the trading volume index and the price per share as dependent variables, for the purposes of verifying the research hypotheses. Climate change is likely to have a significant impact on stock market indices over the coming decades, as the effects become more pronounced and governments take more action to address the issue. Investors will need to carefully consider the risks and opportunities presented by climate change when making investment decisions.
Keywords: climate change , stock market indices , Temperature , precipitation , trading volume index , market value index.